PENINGKATAN KUALITAS MANAJEMEN BERBASIS SEKOLAH MELALUI PELATIHAN TEAM WORK BUILDING BAGI KEPALA SMK SEBAGAI MANAJER PENDIDIKAN - KI Ismara (Teknologi dan Kejuruan, 2012)
Abstract: The success of an educational organization is highly determined by the quality of team work. The SMK principal as one of important components in the success of academic services, needs to encompass the competitive ability of school-based education management. This purpose is hopefully attained by the training simulation of team work building in term of affective, cognitive, and psycho-motoric. The results of training of team work building in some profit and non-profit educational institutions indicate a positive output and outcome trends. The output can reduce some personal conflicts, trait and habit, and other personal potencies that potentially become an obstacle in work productivity, work satisfaction, and work motivation as a team. The outcome can be an consciousness and awareness toward the needs to change self performance and work setting of academic services by new ‘investment’ of corporate values.